2019
DOI: 10.1590/1414-431x20198079
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex sensitivity in frailty syndrome

Abstract: Frailty is related to a decrease in the physiological reserves, which causes difficulties in maintaining homeostasis. An example of physiological mechanisms for cardiovascular homeostasis is the baroreflex. The aim of this study was to compare baroreflex among frail, prefrail, and nonfrail individuals, in supine and orthostatic positions. Community-dwelling older adults were evaluated and categorized into frail, prefrail, or nonfrail groups, according to frailty phenotype. The RR interval (RRi) and systolic bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
1
5
1
Order By: Relevance
“…Heart rate variability complexity is generally expected to decrease with pathology [ 51 ]; however, in the present work, higher entropy in both BP and HR were found to be associated with increased frailty. We postulate that entropy calculated in short length neurocardiovascular data, as reported herein, is not measuring system flexibility, but rather systemic disorder, or “jitter”, resulting from dysregulation of the neurocardiovascular system.…”
Section: Discussioncontrasting
confidence: 61%
“…Heart rate variability complexity is generally expected to decrease with pathology [ 51 ]; however, in the present work, higher entropy in both BP and HR were found to be associated with increased frailty. We postulate that entropy calculated in short length neurocardiovascular data, as reported herein, is not measuring system flexibility, but rather systemic disorder, or “jitter”, resulting from dysregulation of the neurocardiovascular system.…”
Section: Discussioncontrasting
confidence: 61%
“…An example of this is the orthostatic hypotension described in frail individuals ( 33 ). Considering that the baroreflex represents an interaction among control subsystems responsible for BP homeostasis ( 34 ), in agreement with a previous study ( 12 ), our data suggested there is also an impairment in BRS in prefrail individuals.…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, one of the physiological systems most studied is the cardiovascular system (7,9). It has already been demonstrated that frail older adults present impairment in cardiac complexity (5,10,11) and in BRS (12).…”
Section: Introductionmentioning
confidence: 99%
“…We will also perform frailty assessment in elderly patients to explore the role of frailty in the association of autonomic regulation and PIH. 24 Overall, this cohort study will provide the relationship between perioperative assessment of autonomic function and outcomes.…”
Section: Introductionmentioning
confidence: 99%